2006
DOI: 10.1152/ajplung.00435.2005
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling identifies regulatory pathways involved in the late stage of rat fetal lung development

Abstract: Fetal lung development is a complex biological process that involves temporal and spatial regulations of many genes. To understand the molecular mechanisms of this process, we investigated gene expression profiles of fetal lungs on gestational days 18, 19, 20, and 21, as well as newborn and adult rat lungs. For this analysis, we used an in-house rat DNA microarray containing 6,000 known genes and 4,000 expressed sequence tags (ESTs). Of these, 1,512 genes passed the statistical significance analysis of microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
(87 reference statements)
3
17
0
Order By: Relevance
“…Our previous real-time PCR and Western blot results have shown that PTN mRNA and protein expression levels were high at the late stage of fetal lung development (19). The current detailed immunohistochemical studies of fetal lungs at different stages confirmed that PTN was mainly expressed in mesenchymal cells surrounding the epithelium at E18 to E20.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our previous real-time PCR and Western blot results have shown that PTN mRNA and protein expression levels were high at the late stage of fetal lung development (19). The current detailed immunohistochemical studies of fetal lungs at different stages confirmed that PTN was mainly expressed in mesenchymal cells surrounding the epithelium at E18 to E20.…”
Section: Discussionsupporting
confidence: 68%
“…PTN is expressed in fetal lungs (10) and lung cancer cell lines (18). Our DNA microarray analysis of fetal lungs reveals that ptn is highly expressed during the late stage of fetal lung development (19). This is confirmed by real-time PCR and Western blot.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Mouse Lhx3a and Lhx3b mRNAs have distinct temporal expression profiles during development and are differentially expressed in cell lines that model the specialized pituitary cell types (Zhadanov et al, 1995a;Sloop et al, 1999;Sloop et al, 2001a;West et al, 2004). During rodent embryogenesis, Lhx3 mRNAs can be detected in the ventral spinal cord, the pons, the medulla oblongata, the pineal gland, the lungs, and in the developing and established anterior/intermediate pituitary gland (Seidah et al, 1994;Bach et al, 1995;Zhadanov et al, 1995a;Meier et al, 1999;Weng et al, 2006). Similar expression patterns are seen during human development (Sloop et al, 1999;Schmitt et al, 2000;Sobrier et al, 2004).…”
Section: Lhx3mentioning
confidence: 87%